Evaluation of Tubularized Incised Plate Urethroplasty with Spongioplasty–Dartosoraphy Reinforcement in Pediatric Hypospadias: A Randomized Controlled Study - Daboos, Mohammad; Abdelmaboud, Mohamed; Azab, Ahmed; Abdelaziz, Mohamed; Eldamanhory, Hany (European Journal of Pediatric Surgery, 2024)
Introduction The original description of tubularized incised plate urethroplasty (TIPU) was provided by Snodgrass in 1994. The results were significantly improved by several modifications. To decrease the incidence of complications, interposing a vascularized flap after tubularization of the neourethra is recommended. The extent to which the type of interposed tissue has a direct effect on the rate of complications and cosmetic outcomes after TIPU repair is considered the answer to the main hypothesis of this study.Materials and Methods This prospective controlled randomized trial was conducted in the Department of Pediatric Surgery, Al-Azhar University, Cairo, Egypt, between May 2019 and May 2023. A total of 220 patients were included in this study. Patients were randomly assigned to either group A or group B. Group A included 110 patients who underwent TIPU with spongioplasty–dartosoraphy reinforcement. The other 110 patients (group B) underwent TIPU with dorsal dartos flap interposition, without spongioplasty.Results Complications developed in 34 of 220 patients (15.4%). In group A, complications developed in 11 of 110 patients (10.0%). In group B, complications occurred in 23 of 110 patients (20.9%). Although the fistula rate, glanular dehiscence, disruption, and meatal stenosis were not significantly different between the study groups, the skin necrosis rate was significantly lower in group A than in group B. The overall complication rate was significantly lower in group A than in group B. Also, the difference in the mean Hypospadias Objective Scoring Evaluation between the two groups was statistically significant.Conclusion TIPU with spongioplasty–dartosoraphy reinforcement is an effective modification of conventional TIPU. This modification appears to reduce the rate of complications and yield better cosmetic outcomes.
Keywords: pediatric surgery; distal and midpenile hypospadias; spongioplasty; HOSE score